Pulmonary thromboembolism: a case report and misdiagnosis analysis of a 63-year-old female patient - Deng, Yingli; Lai, Jing; He, Qingmin (Frontiers in Medicine, 2024)
This paper presents a case of a 63-year-old female patient who was initially misdiagnosed with mycoplasma pneumonia due to symptoms such as chest pain, hemoptysis, and fever, but was later confirmed to have pulmonary thromboembolism (PTE) through further examination. This case highlights the similarities between PTE and pneumonia in terms of symptoms, as well as the complexity of PTE diagnosis. The article provides a detailed description of the patient’s medical history, symptoms, examination process, and treatment outcomes. Furthermore, it discusses the possible reasons for the misdiagnosis, including insufficient awareness of PTE among physicians, lack of in-depth investigation into the causes of abnormally elevated D-dimer levels, the non-specific clinical manifestations of PTE, and the concerns of the patient’s family regarding pulmonary artery CTA examination. Additionally, the article emphasizes the importance of clinicians in improving their ability to differentiate and diagnose PTE, rationally utilizing clinical examination methods, and ensuring timely diagnosis and treatment of PTE.